Technické aspekty fluorescenční angiografie pro peroperační hodnocení perfuze anastomózy v kolorektální chirurgii - Martínek, L; Pazdírek, F; Hoch, J; Kocián, P (Rozhledy v chirurgii, 2018)
INTRODUCTION: Anastomotic leak after colorectal surgery is a serious complication. Tissue perfusion plays a key role for anastomotic healing. Fluorescence angiography with indocyanine green under near-infrared excitation allows a real-time perfusion assessment. The aim of this study was to evaluate the feasibility and the potential benefit of intraoperative assessment of anastomotic perfusion in colorectal surgery using indocyanine green-enhanced fluorescence in near-infrared light. METHODS: 53 patients with primary anastomosis after elective colon or rectum resection were enrolled between 1 January 2016 and 31 January 2017. Near-infrared fluorescence angiography with indocyanine green was performed to assess tissue perfusion. The data of patient characteristics, data of surgery, data related to perioperative fluorescence angiography and postoperative complications were collected prospectively. RESULTS: Intraoperative fluorescence angiography was successful in 52 patients (98%). There were no adverse effects related to procedure. The mean time from indocyanine green application to visible fluorescence was 35 seconds, the mean added procedure time was 5 minutes. The best contrast was achieved by reducing the dose to 0.1 mg/kg. In 5 patients (9%), fluorescence angiography resulted in a change of the surgical plan. In two cases, the resection line was moved proximally, in two cases the anastomosis was corrected and in one case perfect perfusion of the anastomosis contributed to the decision to abandon the planned protective ileostomy. There was no postoperative anastomotic leak. CONCLUSIONS: Perioperative assessment of anastomotic perfusion in colorectal surgery by use of indocyanine green in near-infrared light is technically feasible with the potential to alter surgical strategy (including avoidance of defunctioning stoma) and to reduce the anastomotic leak rate.Key words: anastomotic leak colorectal surgery fluorescence angiography indocyanine green.
Keywords: Colorectal Neoplasms; kolorektální nádory; netěsnost anastomózy; lidé; indokyanová zeleň; anastomóza chirurgická; Anastomotic Leak; Indocyanine Green; fluoresceinová angiografie; Anastomosis, Surgical; Fluorescein Angiography; Humans